Volume 6B: Materials and Fabrication 2017
DOI: 10.1115/pvp2017-66152
|View full text |Cite
|
Sign up to set email alerts
|

Spent Fuel Canister Probabilistic Confinement Integrity Assessment

Abstract: A probabilistic model was developed that considers the likelihood of through-wall penetration of chloride-induced stress corrosion cracking (CISCC) in austenitic stainless steel canisters and compares different population-based sample inspection regimes. This paper describes the inputs and methods used to simulate multiple canisters with a range of susceptibilities. This paper also summarizes results of key illustrative cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…No evidence of pitting or CISCC on canisters due to corrosion has been observed to date. However, probabilistic approaches that consider the likelihood of through-wall penetration as a result of CISCC in austenitic stainless steel canisters [12] used to identify selection criteria for inspections suggest the potential does exist.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…No evidence of pitting or CISCC on canisters due to corrosion has been observed to date. However, probabilistic approaches that consider the likelihood of through-wall penetration as a result of CISCC in austenitic stainless steel canisters [12] used to identify selection criteria for inspections suggest the potential does exist.…”
Section: Introductionmentioning
confidence: 99%
“…For stainless steels, it is commonly concluded that canisters are highly tolerant of flaws. However, when residual stress is included as part of the loading in the analysis and if consideration is given to elastic-plastic fracture mechanics through the Failure Assessment Diagram (FAD) formulation [8], the instability crack sizes are significantly reduced from those based on the net section yielding limit load failure criterion and more conventional code based analyses [7,12]. Hence, accurate and reliable crack growth velocities become of increasing importance for reliable flaw disposition.…”
Section: Introductionmentioning
confidence: 99%